Health, Education and Industrial Output in Nigeria: An Interactive Effect - Omitogun, Olawunmi; Longe, Adedayo Emmanuel (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This study investigates the interactive impact of human capital investment and industrial output in Nigeria during the period 1990-2013. Various econometrics techniques were used to analysed the data sourced from the Central Bank of Nigeria (CBN) statistical bulletin (2013). The findings revealed that health and education expenditure interactively within the time under study impacted positively and significantly on manufacturing output. Government investment proxy as gross capital formation had a positive and significant effect on manufacturing output. Exchange rate had a negative impact on manufacturing output. The Johansen co-integration technique showed that a long-run co-movement relationship exists between the variables employed in the study. The study concludes that human capital investment plays a significant role in the growth of the manufacturing sector. The major recommendation was that, government should increase its expenditure on health and education expenditure in Nigeria, in order to increase the manufacturing sector output. Keywords: Education and Health Expenditure, Industrial Output, Exchange rate, and Gross Capital Formation.